2017
DOI: 10.1007/s00380-017-0995-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systolic and diastolic properties of hypertensive heart failure using speckle-tracking echocardiography with high volume rates

Abstract: Left ventricular (LV) properties in hypertension (HTN) could be deteriorated by pressure overload, especially in endocardium, resulting in hypertensive heart failure (HHF). We sought to noninvasively examine LV systolic and diastolic functions at three myocardial layers in HTN and elucidate features of HHF by speckle-tracking echocardiography (STE) with high volume rates. We examined normotensive controls (n = 54), HTN patients without LV hypertrophy (LVH) (n = 50), and HTN patients with LVH (n = 40) and HHF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The initial search produced 103 studies and with one identified through other sources, 104 studies were screened and then relevant studies were assessed and evaluated for inclusion (Figure 1). Eight studies were included for quantitative synthesis (Table 1) [17,[19][20][21][22][23][24][25][26]. Excluded were studies that focused on HFpEF in animal models [23].…”
Section: Resultsmentioning
confidence: 99%
“…The initial search produced 103 studies and with one identified through other sources, 104 studies were screened and then relevant studies were assessed and evaluated for inclusion (Figure 1). Eight studies were included for quantitative synthesis (Table 1) [17,[19][20][21][22][23][24][25][26]. Excluded were studies that focused on HFpEF in animal models [23].…”
Section: Resultsmentioning
confidence: 99%
“…The full text review eliminated 32 reports, and 4 articles were added by ‘hand searching’ and examination of bibliographies of existing papers, eventually, 19 articles could be included in the systematic review. 18 studies had a control group and one study compared patients with hypertension with and without left ventricular hypertrophy [ 19 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] ( Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For studies of left ventricular strain, the patient characteristics of the studies demonstrate a range of mean ages, from 29 to 70 years (Table 1 , Ref. [ 19 , 20 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]). The majority of studies had a mean age in the 50 years age group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It enables us to evaluate myocardial deformity and thereby the assessment of global and regional functions. There has been a technological transition of myocardial deformation analysis from tissue Doppler imaging to two-dimensional (2D) 1 and the latest three-dimensional (3D) speckle tracking echocardiography (STE) methods. 2 Despite significant improvements in available HF treatment regimens, the 12-month all-cause mortality of 17% in hospitalized patients and 7% in stable or ambulatory patients remains high.…”
Section: Introductionmentioning
confidence: 99%